Dusty disc–planet interaction with dust-free simulations. Issue 2 (4th May 2018) - Chen, Jhih-Wei; Lin, Min-Kai
ABSTRACT: Protoplanets may be born into dust-rich environments if planetesimals formed through streaming or gravitational instabilities, or if the protoplanetary disc is undergoing mass-loss due to disc winds or photoevaporation. Motivated by this possibility, we explore the interaction between low-mass planets and dusty protoplanetary discs with focus on disc–planet torques. We implement Lin & Youdin's newly developed, purely hydrodynamic model of dusty gas into the pluto code to simulate dusty protoplanetary discs with an embedded planet. We find that for imperfectly coupled dust and high metallicity, e.g. Stokes number 10 −3 and dust-to-gas ratio Σd /Σg = 0.5, a 'bubble' develops inside the planet's co-orbital region, which introduces unsteadiness in the flow. The resulting disc–planet torques sustain large amplitude oscillations that persists well beyond that in simulations with perfectly coupled dust or low dust-loading, where co-rotation torques are always damped. We show that the desaturation of the co-rotation torques by finite-sized particles is related to potential vorticity generation from the misalignment of dust and gas densities. We briefly discuss possible implications for the orbital evolution of protoplanets in dust-rich discs. We also demonstrate Lin & Youdin's dust-free framework reproduces previous results pertaining to dusty protoplanetary discs, including dust-trapping by pressure bumps, dust-settling, and the streaming instability.